A randomised trial of Acceptance and Commitment Therapy for Anorexia Nervosa after daycare treatment, including five-year follow-up. Issue 1 (December 2016) - Parling, Thomas; Cernvall, Martin; Ramklint, Mia; Holmgren, Sven; Ghaderi, Ata
Abstract Background No specific psychotherapy for adult anorexia nervosa (AN) has shown superior effect. Maintenance factors in AN (over-evaluation of control over eating, weight and shape) were addressed via Acceptance and Commitment Therapy (ACT). The study aimed to compare 19 sessions of ACT with treatment as usual (TAU), after 9 to 12 weeks of daycare, regarding recovery and risk of relapse up to five years. Methods Patients with a full, sub-threshold or partial AN diagnosis from an adult eating disorder unit at a hospital were randomized to ACT (n = 24) and TAU (n = 19). The staff at the hospital, as well as the participants, were unaware of the allocation until the last week of daycare. Primary outcome measures were body mass index (BMI) and specific eating psychopathology. Analyses included mixed model repeated measures and odds ratios. Results Groups did not differ regarding recovery and relapse using a metric of BMI and the Eating Disorder Examination Questionnaire (EDE-Q). There were only significant time effects. However, odds ratio indicated that ACT participants were more likely to reach good outcome. The study was underpowered due to unexpected low inflow of patients and high attrition. Conclusion Longer treatment, more focus on established perpetuating factors and weight restoration integrated with ACT might improve outcome. Potential pitfalls regarding future trials on AN are discussed. Trial registration number ISRCTN 12106530. Retrospectively registered 08/06/2016.